2020
DOI: 10.1186/s13287-020-01873-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles acquired during cell expansion and licensing validate mesenchymal stromal cell lineage genes

Abstract: Background Mesenchymal stromal cells (MSCs) are rapidly advancing as commercial therapeutics. However, there are still no adequate tools to validate the identity of MSCs and support standardization of MSC-based products. Currently accepted metrics include cell surface marker profiling and tri-lineage differentiation assays, neither of which is definitive. Transcript profiling represents a cost- and time-effective approach amenable to MSC manufacturing processes. Two independent labs recently repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Similar stromal cells with salient features of CAR cells have been identified in human adult BM (10,71). In line with these findings, the CXCL12/CXCR4 axis is key in immunosuppression and metastatic spread in solid tumors, through reciprocal crosstalk between FAP High CAFs and regulatory T cells (Tregs), as well as FAP High CAFs and cancer cells, respectively (24,25,27).…”
Section: Niche Cytokines and Chemokinessupporting
confidence: 72%
See 2 more Smart Citations
“…Similar stromal cells with salient features of CAR cells have been identified in human adult BM (10,71). In line with these findings, the CXCL12/CXCR4 axis is key in immunosuppression and metastatic spread in solid tumors, through reciprocal crosstalk between FAP High CAFs and regulatory T cells (Tregs), as well as FAP High CAFs and cancer cells, respectively (24,25,27).…”
Section: Niche Cytokines and Chemokinessupporting
confidence: 72%
“…Similar stromal cells with salient features of CAR cells have been identified in human adult BM ( 10 , 71 ). In line with these findings, the CXCL12/CXCR4 axis is key in immunosuppression and metastatic spread in solid tumors, through reciprocal crosstalk between FAP High CAFs and regulatory T cells (Tregs), as well as FAP High CAFs and cancer cells, respectively ( 24 , 25 , 27 ). In addition to CXCR4 and CXCL12, numerous studies have shown that chemokines act at different levels in the progression of the primary tumor, modulating both tumor cell proliferation, apoptosis, invasion, angiogenesis, recruitment of immune cells and resistance to chemotherapy ( 72 76 ).…”
Section: Niche Cytokines and Chemokinesmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, increasing attention is being focused on mesenchymal stem cell (MSC) therapy. MSCs are specific types of cells under exploration for treatment of human diseases and have been found in tissues including adipose tissue ( 14 ), peripheral blood ( 15 , 16 ), dental pulp ( 17 ), bone marrow ( 18 ), and neonatal tissues, especially in parts of the placenta ( 19 ) and umbilical cord ( 20 , 21 ). The definition of MSCs involves three features: Self-renewal ability; Multi-differentiation potential; Specific surface biomarkers ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing of MSCs for therapeutic purposes often includes extended cell-expansion or inflammatory licensing. Although these cytokines, chemokines, regulatory mediators and TLR candidate genes are known [ 14 ], their profile and modulation under the pressures of cell-expansion and immune activation combination has not been formally investigated. Herein, we have investigated the impact of a combination of inflammation and cell-expansion signals on the transcript profile of genes linked to the immuno-reparative features of AT-MSCs.…”
Section: Introductionmentioning
confidence: 99%